Exploring the Anti-quorum Sensing and Antibiofilm Efficacy of Phytol against Serratia marcescens Associated Acute Pyelonephritis Infection in Wistar Rats - Srinivasan, Ramanathan; Mohankumar, Ramar; Kannappan, Arunachalam; Karthick Raja, Veeramani; Archunan, Govindaraju; Karutha Pandian, Shunmugiah; Ruckmani, Kandasamy; Veera Ravi, Arumugam (Frontiers in Cellular and Infection Microbiology, 2017)
Quorum Sensing (QS) mechanism, a bacterial density-dependent gene expression system, governs the Serratia marcescens pathogenesis through the production of virulence factors and biofilm formation. The present study demonstrates the anti-quorum sensing (anti-QS), antibiofilm potential and in vivo protective effect of phytol, a diterpene alcohol broadly utilized as food additive and in therapeutics fields. In vitro treatment of phytol (5 and 10 μg/ml) showed decreasing level of biofilm formation, lipase and hemolysin production in S. marcescens compared to their respective controls. More, microscopic analyses confirmed the antibiofilm potential of phytol. The biofilm related phenomenons such as swarming motility and exopolysccharide productions were also inhibited by phytol. Furthermore, the real-time analysis elucidated the molecular mechanism of phytol which showed downregulation of fimA, fimC, flhC, flhD, bsmB, pigP, and shlA gene expressions. On the other hand, the in vivo rescue effect of phytol was assessed against S. marcescens associated acute pyelonephritis in Wistar rat. Compared to the infected and vehicle controls, the phytol treated groups (100 and 200 mg/kg) showed decreased level of bacterial counts in kidney, bladder tissues and urine samples on the 5th post infection day. As well, the phytol treatment showed reduced level of virulence enzymes such as lipase and protease productions compared to the infected and vehicle controls. Further, the infected and vehicle controls showed increasing level of inflammatory markers such as malondialdehyde (MDA), nitric oxide (NO) and myeloperoxidase (MPO) productions. In contrast, the phytol treatment showed decreasing level of inflammatory markers. In histopathology, the uninfected animal showed normal kidney and bladder structure, wherein, the infected animals showed extensive infiltration of neutrophils in kidney and bladder tissues. In contrast, the phytol treatment showed normal kidney and bladder tissues. Additionally, the toxic effect of phytol (200 mg/kg) was assessed by single dose toxicity analysis. No changes were observed in hematological, biochemical profiles and histopathological analysis of vital organs in phytol treated animals compared to the untreated controls. Hence, this study suggested the potential use of phytol for its anti-QS, antibiofilm and anti-inflammatory properties against S. marcescens infections and their associated inflammation reactions.